Midwives' voices on early initiation of antenatal care following a positive gravindex test: A qualitative study - Rhulani S Shinyawani; Thivhulawi N Malwela; Maria S Maputle (Wolters Kluwer Medknow Publications, 2023)
Background: Early Antenatal Care (ANC) initiation is aimed at improving maternal and perinatal health outcomes through the identification of complications and determining the level of care needed. This study aimed to determine the voices of midwives on the provision of early initiation of ANC following positive gravindex. Materials and Methods: The phenomenology approach underpinned the study. The participants included midwives providing ANC at health facilities under Tshino-Mutsha local area in May-December 2020. Nonprobability, purposive sampling was used to select four clinics and to sample 20 midwives. Semistructured face-to-face, in-depth interviews were conducted using an interview guide. Data saturation was reached at Participant 15; however, the researcher continued until Participant 20. Trustworthiness was ensured and ethical principles were adhered to. Data analysis was done using Tesch's open coding approach. Results: Two themes and seven subthemes emerged, as challenges related to the provision of midwifery practice and to pregnant women. The seven subthemes were the shortage of resources, poor support of midwives, poor adherence to the available protocol for the provision of ANC, blaming of midwives by management and community, late ANC booking by pregnant women, denial of pregnancy by young women ignorance leading to a general resistance to ANC instructions, hence late booking Conclusions: It was concluded that shortage of human and material resources hindered the initiation of early ANC to detect, prevent, and manage the existing and potential causes of maternal and newborn mortality and morbidity.